Teaching Students to Teach: A Case Study from the Yale University Art Gallery. (October 2015) - Manekin, Elizabeth; Williams, Elizabeth
<x content-type="archive" xml:space="preserve">Abstract</x> The way the Yale University Art Gallery engages students and the adult public has shifted profoundly over time, a change reflected in the evolution of the museum's signature Gallery Guide program. Founded in 1998 as an organic, experimental way to better engage Yale students to give lecture-based tours, it is now a structured, well-articulated model for training students to teach the adult public from original works of art. This article presents a detailed exploration of the program's evolution, its core training principles and learning outcomes; it also raises questions for the future as the museum considers new ways of engaging students and expanded adult audiences, a conversation with implications for all types of museums. Ultimately, this case study illustrates that while training undergraduates to teach the adult public takes a great deal of staff time and effort, it yields stronger, more dynamic pedagogy and makes the Yale University Art Gallery a more vibrant teaching institution.